INTENSIVE CARE FOR THE CRITICAL PATIENT - Xavier Arruda Costa, Yasmim; Barcelos Lima Cardoso, Rafael; Bassi Martini, Paulo; Rezende Franco , Ítalo; de Cássia Sousa Teixeira da Silva, Mary; kledja Sousa e Sousa Costa , Mylena; Saphira Araújo Costa, Alynne; Cândida de Araújo Molinero, Fernanda; Rodrigues da Fonseca , Fabiana; Eliana Waltermann, Martha (Health and Society, 2023)
Introduction: In the context of modern medicine, intensive care is often the front line in treating patients with life-threatening conditions. From its initial conception, when intensive care units (ICUs) emerged as a response to the need for a more concentrated and specialized approach to critically ill patients, to the technological and therapeutic advances that characterize contemporary intensive care, the evolution of this discipline has been remarkable. Objective: To examine current approaches to intensive care for critically ill patients. Methodology: This is an integrative review study, carried out according to scientific data collection: LILACS, SCIELO and MEDLINE. Results and Discussions: The results indicate that technological advances are transforming intensive care. Advanced monitoring equipment allows constant surveillance of patients’ vital signs and clinical parameters. This not only improves the early detection of complications, but also helps to adapt treatment in a more precise and personalized way. Conclusion: In the current medical scenario, intensive care for critically ill patients continues to play an invaluable role in preserving lives and seeking to recover individuals in extremely challenging health states. One of the most notable findings is the continuous evolution of intensive care, both in terms of complexity and effectiveness.